PENERAPAN KNOWLEDGE SHARING UNTUK MEMBENTUK SHARING CULTURE PADA PT. JANE INDAH PERKASA JAKARTA - Mia Rosmiati (LPPM STMIK ANTAR BANGSA, 2015)
Abstract— Knowledge as one of the company's assets is one aspect that can increase the value of a company's competitive advantage. Knowledge becomes important when the competition among enterprises and labor exchange happened so fast, it is necessary for a form of knowledge management system or better known as Knowledge Sharing. The importance of knowledge management is also realized by PT. Jane Indah Perkasa Jakarta so that this research aims to apply knowledge sharing in the company. The method of this research is quantitative descriptive supported by the method of The Most Admired Knowledge Enterprise (MAKE). Results of this study based on questionnaires on the application of Knowledge Sharing to employees that are at intervals of 3.40 to 4.19, the average value of the entire statement at 4.19 which was well received.